Compound Chinese medicine (F1) improves spleen deficiency diarrhea by protecting the intestinal mucosa and regulating the intestinal flora - Wang, Kang; Li, Guanzong; Yang, Zhi; Yang, Fumei; Sun, Yulin; Duan, Gang; Sun, Wang; Zhou, Ke; He, Jun; Dai, Feiyan (Frontiers in Microbiology, 2024)
Compound Chinese medicine (F1) is a traditional prescription in Chinese medicine that is commonly used to treat spleen deficiency diarrhea (SDD). It has demonstrated remarkable effectiveness in clinical practice. However, the precise mechanism by which it exerts its antidiarrheal effect is still unclear. This study aimed at investigating the antidiarrheal efficacy and mechanism of F1 on senna-induced secretory diarrhea (SDD). Senna was utilized to induce the development of a mouse model of senna-induced secretory diarrhea (SDD) in order to observe the rate of diarrhea, diarrhea index, blood biochemistry, and histopathological changes in the small intestine. Additionally, the levels of sodium and hydrogen exchange protein 3 (NHE3) and short-chain fatty acids (SCFAs) were determined using enzyme-linked immunosorbent assay (ELISA). The impact of F1 on the senna-induced SDD mouse models was evaluated by monitoring changes in the gut microbiota through 16S rRNA (V3-V4) sequencing. The results demonstrated that F1, a traditional Chinese medicine, effectively increased the body weight of SDD mice and reduced the incidence of diarrhea and diarrhea index. Additionally, F1 restored liver and kidney function, reduced the infiltration of inflammatory cells in intestinal tissue, and promoted the growth of intestinal villi. Furthermore, F1 was found to enhance the expression of NHE3 and SCFAs. It also increased the abundance of Firmicutes and Lactobacillus species, while decreasing the abundance of Proteobacteria and Shigella.